Cognitive impairment and dementia—Are they linked to childhood health and socioeconomic status? A systematic review - Tung Le; Asri Maharani; Mark Hayter; James Gilleen; Amanda Lee (PLoS ONE, 2025)
Background Dementia is a major public health concern, with its incidence rising as the population ages. Recent studies suggest links between childhood health, socioeconomic status, and later-life cognitive impairment and dementia, though findings remain inconclusive. This systematic review evaluates the influence of childhood health and socioeconomic status on cognitive impairment and dementia. Method and findings A systematic search conducted in MEDLINE, CiNAHL, and PsycINFO in December 2024 identified 44 studies matching our inclusion criteria. Findings are presented under five key themes: (1) childhood health, (2) childhood educational attainment, (3) family socioeconomic and educational factors, (4) childhood experiences, and (5) childhood reading habits and social interactions. Conclusion Our results highlight the need for further longitudinal studies to establish causal relationships between early-life risk factors and later cognitive decline. Policymakers should prioritize early childhood development programs that integrate health, nutrition, education, and social support to help mitigate cognitive impairment and dementia in later life.